The erotic in the literature of medieval Britain - Hopkins, Amanda, 1962-; Rushton, Cory (D.S. Brewer, 2007)
This edited work provides an examination of the erotic in medieval literature which includes articles on the role of clothing and nudity, the tension between eroticism and transgression and religion and the erotic.